Decompressive craniectomy following subarachnoid hemorrhage: A prospective Swedish multicenter study - Bryndís Baldvinsdóttir; Erik Kronvall; Elisabeth Ronne-Engström; Per Enblad; Paula Klurfan; Johanna Eneling; Peter Lindvall; Helena Aineskog; Steen Friðriksson; Mikael Svensson; Peter Alpkvist; Jan Hillman; et al. (Brain and Spine, 2025)
Introduction: Decompressive craniectomy (DC) in patients with severe aneurysmal subarachnoid hemorrhage (aSAH) can be a life-saving procedure. The aim of this nationwide prospective study was to investigate the use of DC in aSAH patients in Sweden. Research question: To explore the risk factors and functional outcome associated with DC in patients with aSAH. Material and methods: Patients treated for aSAH at all neurosurgical centers in Sweden during a 3.5-year period (2014–2018) were prospectively registered. Clinical, radiological and treatment-related factors with regard to DC were analyzed using Chi-Square and logistic regression analysis. Functional outcome was assessed by the extended Glasgow outcome scale one year after the bleeding. Results: During the study period, 1037 patients were treated for aSAH. Thirty-five patients (3.4%) underwent DC. At one year follow-up, 25 of these (71%) had unfavorable functional outcome. Multivariate logistic regression analysis revealed that poor clinical grade before aneurysm treatment, middle cerebral artery (MCA) aneurysm, edema on the initial computed tomography (CT), and adverse events during aneurysm occlusion were independent and significant risk factors for performing DC. Discussion and conclusion: DC is relatively uncommon in aSAH patients and is related to increased risk of unfavorable outcome. However, favorable functional outcome was seen in 29% of patients with DC. Adverse events during aneurysm occlusion were significant risk factors for DC.